Relative usage of tense form of the verb in Ukrainian and German (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the research the relative usage, quantity and distinction of tense forms of the verb in Ukrainian and German are examined.
Keywords: tense form of the verb; relative usage of tense form of the verb